2017
DOI: 10.1016/j.precamres.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Late Neoarchean crust-mantle geodynamics: Evidence from Pingquan Complex of the Northern Hebei Province, North China Craton

Abstract: A late Neoarchean intra-oceanic arc along the northwestern margin of Eastern Block (EB), North China Craton, provides important insights into the nature of Archean mantle sources and crust-mantle geodynamics. The Pingquan Complex and the entire Northern Hebei Province (NHB) are located in the middle part of the arc, and overlap the northern extent of the Trans-North China Orogen. Zircon U-Pb isotopic age data reveal that the Pingquan Complex consists of ~2537-2515 Ma dioritic gneisses, ~2506-2503 Ma amphibolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 157 publications
1
6
0
Order By: Relevance
“…The metamorphic ages of c. 2.5 Ga are consistent with those reported from other Archean basement complexes in the Eastern Block of the NCC (e.g. Zhao et al 1998;Ge et al 2003;Geng et al 2006;Yang et al 2008;Liu et al 2011;Lv et al 2012;Wan et al 2012;Wang et al 2012bWang et al , 2015Wang et al , 2017bWu et al 2013), representing a large-scale end-Neoarchean tectonothermal event related to underplating of large amounts of mantlederived magma in the Eastern Block (Zhao et al 1998;Yang et al 2008;Wu et al 2013;Wang et al 2015). On the other hand, similar late Palaeoproterozoic metamorphic ages have been found in nearly all the major basement lithologies in the study area (Xu et al 2006;Guo & Li, 2009;Liu et al 2009Liu et al , 2017cLiu et al , 2018Wan et al 2010;Fig.…”
Section: A Geochronological Framework Of the Bengbu And Huoqiu Areassupporting
confidence: 88%
“…The metamorphic ages of c. 2.5 Ga are consistent with those reported from other Archean basement complexes in the Eastern Block of the NCC (e.g. Zhao et al 1998;Ge et al 2003;Geng et al 2006;Yang et al 2008;Liu et al 2011;Lv et al 2012;Wan et al 2012;Wang et al 2012bWang et al , 2015Wang et al , 2017bWu et al 2013), representing a large-scale end-Neoarchean tectonothermal event related to underplating of large amounts of mantlederived magma in the Eastern Block (Zhao et al 1998;Yang et al 2008;Wu et al 2013;Wang et al 2015). On the other hand, similar late Palaeoproterozoic metamorphic ages have been found in nearly all the major basement lithologies in the study area (Xu et al 2006;Guo & Li, 2009;Liu et al 2009Liu et al , 2017cLiu et al , 2018Wan et al 2010;Fig.…”
Section: A Geochronological Framework Of the Bengbu And Huoqiu Areassupporting
confidence: 88%
“…Thus, the Northern Liaoning Terrane likely accreted onto the northern continental margin of NCC after ~2530 Ma, marking final stabilization of the regional continental crust (Figure b). Similarly, a late Neoarchean intra‐oceanic arc system was proposed for the region southwest of Northern Liaoning Terrane (Western Liaoning, Zunhua‐Qinglong Block of Eastern Hebei, and Wutai Complex), which accreted onto the >2.7 Ga continental nucleus of Eastern Block at the end of the Archean [ Liu et al ., ; W. Wang et al ., , , , ; Guo et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a late Neoarchean intra-oceanic arc system was proposed for the region southwest of Northern Liaoning Terrane (Western Liaoning, Zunhua-Qinglong Block of Eastern Hebei, and Wutai Complex), which accreted onto the >2.7 Ga continental nucleus of Eastern Block at the end of the Archean [Liu et al, 2006;W. Wang et al, , 2015W. Wang et al, , 2017Guo et al, 2013].…”
Section: Late Neoarchean Accretionary Orogen and Continental Growthmentioning
confidence: 96%
“…Subsequently, the discoveries of ~3.0–2.8‐Ga eclogite inclusions within kimberlites, together with the rapid decrease in the net rate of crustal growth from ~3.2 to 2.7 Ga, indicated that the worldwide onset of plate tectonics occurred during ~3.2–2.7 Ga, although the mantle plume regime still played an important role locally (Dhuime et al, ; Naeraa et al, ; Rollinson, ; Shirey & Richardson, ; Van Kranendonk, ). Based on detailed investigations of field mapping, petrology, and geochemistry in the past 20 years, an ~2.6–2.5 Ga more than 1,000‐km length NNE‐SSW‐trending intraoceanic arc system has been described in the northwestern margins of the eastern North China Craton (ENCC), indicating that the late Neoarchean geodynamic regime was dominated by plate tectonics (Bai et al, , , ; Fu et al, , ; Guo et al, ; Liu et al, , , , , , , , , ; Liu et al, ; Liu et al, ; Wang, ; Wang et al, ; Wang et al, ; Wang et al, ; Wang et al, ; Yongjun et al, ; Zhang et al, ). What geodynamic processes led to transformation of the Hadean‐Paleoarchean mantle plume regime to the Mesoarchean to Neoarchean major plate tectonic regime and how the Archean subduction zones initiated are still unknown, which presents serious barriers to understanding the geodynamic evolution of the early Earth crust.…”
Section: Introductionmentioning
confidence: 99%